KEKUATAN DAN TANTANGAN PERAN ISTRI NELAYAN DALAM AKTIVITAS EKONOMI KELUARGA PESISIR - Dewi, Gessan Kurnia; Lisnarini, Naurah; Utama, Mochhamad Ikhsan Cahya (POLITEKNIK LP3I JAKARTA, 2026)
Coastal areas are characterized by economic vulnerability due to their strong dependence on natural conditions and seasonal sectors such as fisheries and tourism. Fishermen’s wives play a crucial role in sustaining the economic resilience of coastal households. This study aims to analyze the strengths and challenges of fishermen’s wives’ roles in household economic activities in Batu Karas Village, Pangandaran Regency. The research employed a qualitative descriptive approach using qualitative SWOT analysis. Data were collected through in-depth interviews, field observations, and document analysis involving village officials, management of the Mina Rasa Village Cooperative, fishing communities, and fishermen’s wives engaged in economic activities. The findings reveal that fishermen’s wives contribute significantly to the distribution of fishery products, the development of micro-scale businesses, and the diversification of household income sources. Revealed strengths include role flexibility and strong social capital within women’s coastal communities. However, these contributions are constrained by limited financial literacy, business management skills, and restricted access to decision-making processes within formal economic institutions. Meanwhile, the recovery of the coastal tourism sector presents opportunities for the development of value-added fishery products and creative coastal enterprises. This study underscores the importance of strengthening capacity building and institutional integration of fishermen’s wives within coastal economic governance to enhance the long-term economic resilience of fishermen’s households.